The Relationship of Quality of Work-Life With Job Satisfaction of Fashion-Retail Company Employees at PT. X (Jurnal Manajemen Bisnis, 2025)
One of the impacts of globalization in this era is the annual growth of retail industries, expanding to various corners of the country. A critical factor for a company's success in a competitive environment is the condition of its employees. Absenteeism refers to employees being absent from work or avoiding their responsibilities, which can lead to decreased productivity or a decline in morale within the company. It often reflects the quality of work-life in the organization, which in turn indicates the overall satisfaction levels of employees. This study aims to identify the relationship between the quality of work-life and job satisfaction among employees in a fashion retail company. A quantitative approach was employed, using an online questionnaire to collect data, and a simple correlation analysis was conducted. The data collection method involved purposive sampling, with 118 permanent employees from Company X serving as respondents. The results of this study indicate a positive correlation between the quality of work-life and job satisfaction. This finding suggests that as the quality of work-life improves, job satisfaction also increases, and vice versa.